2015
DOI: 10.1002/adfm.201503154
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Mechanism of Water‐Triggered Diplex Transformation and Correlating the Changes in Structures and Separation Properties

Abstract: Recently, great attention has been devoted to the initial and final structures of single‐crystal to single‐crystal (SCSC) transformations and dissolution‐recrystallization structural transformations (DRSTs), whereas the isolation and characterization of crucial intermediates and the unequivocal mechanism of the dynamic conversion process receive comparatively little consideration. Herein, a CuII‐based porous coordination polymer (PCP), which possesses a Kagomé lattice, is solvothermally synthesized. Triggered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Zang et al have revealed that a hexagonal crystalline Cu II ‐based PCP‐1 (PCP=porous coordination polymer), with the 2D Kagomé lattice, undergoes a solvent‐mediated structural transformation to form a strip‐like PCP‐3 crystal with a 3D NbO framework . The whole process follows the core‐on‐shell mechanism.…”
Section: Core‐on‐shell Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Zang et al have revealed that a hexagonal crystalline Cu II ‐based PCP‐1 (PCP=porous coordination polymer), with the 2D Kagomé lattice, undergoes a solvent‐mediated structural transformation to form a strip‐like PCP‐3 crystal with a 3D NbO framework . The whole process follows the core‐on‐shell mechanism.…”
Section: Core‐on‐shell Mechanismmentioning
confidence: 99%
“…Zang et al have revealed that ah exagonal crystalline Cu IIbased PCP-1 (PCP = porous coordination polymer), with the 2D KagomØ lattice,u ndergoes as olvent-mediated structural transformation to form as trip-like PCP-3 crystal with a3 DN bO framework. [14] The whole process follows the core-on-shell mechanism. Crystals of PCP-1 in water first lose their transparency,a nd then the edges of the hexagon will be dissolved, and finally the green strip-like crystalsP CP-3 are recrystallized in situ ( Figure 5).…”
Section: Core-on-shell Mechanismmentioning
confidence: 99%
“…Very few studies exemplify the step-by-step crystal growth process. [18,19] Due to large radii, high and various coordination numbersof alkaline earth metal ions, the relatedCPs are difficult to be predesigneda nd directional synthesized. Especially for Sr 2 + and Ba 2 + ,t hey have received much less attention compared to other transition metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Functional materials featuring abrupt change of their physical and/or chemical properties in response to temperature fluctuation, pressure variation, light, electric/magnetic field, and other external stimuli have attracted great attention in the fields of molecular motors, optoelectronic technology, digital processing, sensors, etc . Most recent studies have been reported to design such materials, and a large number of materials possessing single‐switchable electrical, optical, or magnetic properties have been studied. However, with the development of science and technology, a simple function material has not fully satisfied the needs of application.…”
Section: Introductionmentioning
confidence: 99%